Infectomic Analysis of Gene Expression Profiles of Human Brain Microvascular Endothelial Cells Infected with Cryptococcus neoformans. (13th February 2008) - Jong, Ambrose; Wu, Chun-Hua; Zhou, Wensheng; Chen, Han-Min; Huang, Sheng-He
Abstract : In order to dissect the pathogenesis of Cryptococcus neoformans meningoencephalitis, a genomic survey of the changes in gene expression of human brain microvascular endothelial cells infected by C . neoformans was carried out in a time-course study. Principal component analysis (PCA) revealed sigificant fluctuations in the expression levels of different groups of genes during the pathogen-host interaction. Self-organizing map (SOM) analysis revealed that most genes were up- or downregulated 2 folds or more at least at one time point during the pathogen-host engagement. The microarray data were validated by Western blot analysis of a group of genes, including β -actin, Bcl-x, CD47, Bax, Bad, and Bcl-2. Hierarchical cluster profile showed that 61 out of 66 listed interferon genes were changed at least at one time point. Similarly, the active responses in expression of MHC genes were detected at all stages of the interaction. Taken together, our infectomic approaches suggest that the host cells significantly change the gene profiles and also actively participate in immunoregulations of the central nervous system (CNS) during C . neoformans infection.